Pengaruh Biaya produksi, Biaya Kualitas, Harga Jual dan Modal Kerja Terhadap Laba Bersih Sub Sektor Makanan dan Minuman Yang Terdaftar di Bei Tahun 2018-2025 - Dira Rahdita; Kartika Berliani; Diah Febriyanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study analyzed the effect of production cost, quality cost, selling price and working capital on net profit in food and beverage manufacturing companies listed on the Indonesia Stoxk Exchange (IDX) during the period 2018-2025. Methodology used was a quantitative approach with descriptive and verificative research design. Purposive sampling was to select a sample of 4 manufacturing companies meeting specific criteria over an 8year observation period, resulting in 32 sample data points. Secondary data obtained from annual audited financial reports were analyzed using multiple linear regression, classical assumption test, Pearson product-moment correlation, coefficient of determination, t-test and F-test via SPSS IBM v.26. The result demonstrated that production cost, quality cost, selling price and working capital individually and simultaneously provided significant insights into net profit fluctuations. Managing operational efficiency and pricing strategies proved vital for maintaining profitability amidst raw material price changes.